Evaluation of Diagnoses, Discharge Rates, Follow Up Frequency, and Non-Attendance of South Caerphilly Community Mental Health Team Outpatient Psychiatric Clinics - Mohamed Bader; Rahul Bansal (BJPsych Open, 2025)
Aims: Evaluate the frequency of mental disorders patients present with in different sites in SCCMHT to inform quality improvement to better match patient needs. To assess the non-attendance rate in various sites for future projects to explore factors associated with patient non-attendance. To quantify outcomes following patient reviews to explore discharge/follow up frequency.